2019
DOI: 10.1101/561787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interplay between the human gut microbiome and host metabolism

Abstract: The human gut is inhabited by a complex and metabolically active microbial ecosystem regulating host health. While many studies have focused on the effect of individual microbial taxa, the metabolic potential of the entire gut microbial ecosystem has been largely under-explored. We characterised the gut microbiome of 1,004 twins via whole shotgun metagenomic sequencing (average 39M reads per sample). We observed greater similarity, across unrelated individuals, for functional metabolic pathways (82%) than for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(158 citation statements)
references
References 42 publications
8
150
0
Order By: Relevance
“…In comparison to gut microbial composition, the metabolic profiles were relatively less sensitive to the infant development in terms of sampling time points. Temporal stability of the gut metabolome can be related to the concept of high redundancy of metabolic pathways across different microbial species (33,34). Our finding is also in line with previous literature suggesting that human metabolic profiles are more conserved than gut microbiome (34).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In comparison to gut microbial composition, the metabolic profiles were relatively less sensitive to the infant development in terms of sampling time points. Temporal stability of the gut metabolome can be related to the concept of high redundancy of metabolic pathways across different microbial species (33,34). Our finding is also in line with previous literature suggesting that human metabolic profiles are more conserved than gut microbiome (34).…”
Section: Discussionsupporting
confidence: 90%
“…Temporal stability of the gut metabolome can be related to the concept of high redundancy of metabolic pathways across different microbial species (33,34). Our finding is also in line with previous literature suggesting that human metabolic profiles are more conserved than gut microbiome (34). Elevated serum MMA and stool glucose have been associated with vitamin B12 (35) and carbohydrate malabsorption (36) in children respectively.…”
Section: Discussionsupporting
confidence: 87%
“…38 In addition, the abundance of M. smithii has been recently found to correlate negatively with the percentage of visceral fat. 39 Another large population study reported that Akkermansia, Christensenellaceae, the Tenericutes RF39 and Rikenellaceae are associated with lower serum triglycerides levels in addition to low BMI. 40 Interestingly, we found that the increase of the Archaea Methanobrevibacter and vadinCA11, and the decrease of the genus Dorea, are specifically associated with PWS, and not dependent on BFMI.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome is thought to have host genetic background, cause epigenetic modulations, affect host metabolism and be influenced by environmental exposures . This necessitates integrating the microbiome with other omics layers, such as metabolomics, proteomics, transcriptomics, genomics, epigenomics and exposomics (environmental factors), which will help to provide more insight into the mechanisms of complex disease processes such as asthma.…”
Section: The Asthma Microbiome From Bench To Bedside: Challengesmentioning
confidence: 99%